Penguatan Karakter Anak Dalam Keluarga Dalam Situasi Pandemi Covid-19 - Lailati Nazula; Erni Munastiwi (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2021)
The Covid-19 pandemic situation requires people to do activities from home, including the learning process. Learning from home is a great opportunity for families to take advantage of this situation as a means of strengthening children's character. Strengthening character or also called character education is very important to produce a commendable human, both for himself and his environment. This study aims to explore the use of a pandemic situation as a means of strengthening children's character by parents. With qualitative methods, through a grounded theory approach, this study included three randomly selected participants (random sampling). The data in the study were collected through interviews using open questions. Before the analysis was carried out, the data validity was first checked using the member checking method, followed by analysis using the coding method. From the research conducted, it was found that this pandemic situation could be a means of strengthening children's character by creating independent, responsible, religious, mutual, and nationalist values, becoming a momentum for families to be involved in character education and building harmony with children, making children learn patterns. live clean and healthy, and children are reduced from outside environmental activities that are not useful.